131k views
2 votes
3 (x - 2) = 7 – (4 - x)​

User Nduplessis
by
4.8k points

2 Answers

7 votes

the answer is x = 9/2

Step-by-step explanation

3 (x - 2) = 7 – (4 - x)

apply the distributive law to 3(x - 2)

to get 3x - 6

simplify 7-(4-x)

3 + x

you now have

3x - 6 = x + 3

add 6 to both sides

-6+6=0 3 + 6 = 9

3x=x+9

subtract x from both sides

3x - x = 2x x - x = 0

2x = 9

divide both sides by 2

2x/2 = x 9/2

to get x = 9/2

User Rogers
by
5.3k points
3 votes

Answer:

Isolate the variable by dividing each side by factors that don't contain the variable.

Exact Form:

x=92x=92

Decimal Form:

x=4.5x=4.5

Mixed Number Form:

x=412x=412

User Huibin Zhang
by
5.0k points